Bruxism, Related Factors and Oral Health-Related Quality of Life Among Vietnamese Medical Students - Phuong, Nguyen Thi Thu (Int J Environ Res Public Health, 2020)
Although bruxism is a common issue with a high prevalence, there has been a lack of epidemiological data about bruxism in Vietnam. This cross-sectional study aimed to determine the prevalence and associated factors of bruxism and its impact on oral health-related quality of life among Vietnamese medical students. Bruxism was assessed by the Bruxism Assessment Questionnaire. Temporomandibular disorders were clinically examined followed by the Diagnostic Criteria for Temporomandibular Disorders Axis I. Perceived stress, educational stress, and oral health-related quality of life were assessed using the Vietnamese version of Perceived Stress Scale 10, the Vietnamese version of the Educational Stress Scale for Adolescents, and the Vietnamese version of the 14-item Oral Health Impact Profile, respectively. The prevalence of bruxism, sleep bruxism, awake bruxism, and both conditions in Vietnamese medical students were 51.2%, 38.2%, 23.4%, and 10.4% respectively. Stress, temporomandibular joint pain, masticatory muscle pain, and tooth attrition were associated with the presence of bruxism. Vietnamese medical students were negatively affected by bruxism in terms of oral health-related quality of life.